Implementasi Protokol Keimigrasian: Studi Kasus Enam WNA Asal Vietnam Diamankan Petugas Kanim Kelas I TPI Tanjungpinang - Andika Andika; Jhon Agus Frando Sipayung; Raja Andreas Monang Pardede; Siti Nurafina; Grace Naomi Manullang; Kustiawan Kustiawan (CV. ITTC INDONESIA, 2025)
This study analyzes the implementation of immigration protocols in handling immigration violation cases involving six Vietnamese foreign nationals apprehended by officers from Class I TPI Immigration Office Tanjungpinang in August 2024. The study aims to evaluate the effectiveness of immigration procedure implementation in handling visa and immigration document violations. The research employs a qualitative approach with case study methods, analyzing primary data from official reports and interviews with immigration officers, as well as secondary data from applicable immigration regulations. The findings indicate that the handling of this case has been in accordance with applicable immigration protocols, however challenges remain in inter-agency coordination and regulatory understanding by foreign nationals. This case emphasizes the importance of consistent immigration law enforcement and more comprehensive regulatory socialization to foreign nationals entering Indonesia.